2008
DOI: 10.1073/pnas.0804571105
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cytotoxic T lymphocyte triggering by PIR-B on dendritic cells

Abstract: Priming of cytotoxic T lymphocytes (CTLs) by dendritic cells (DCs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 43 publications
(47 reference statements)
0
38
0
Order By: Relevance
“…Microarray analysis revealed that dermal CD14 + DCs expressed ILT4 and ILT2, known inhibitors of CD8 binding to MHC class I (21,22,28). Indeed, structural modeling demonstrated that ILT2 or ILT4 sterically interfere with CD8-α in binding to MHC class I (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray analysis revealed that dermal CD14 + DCs expressed ILT4 and ILT2, known inhibitors of CD8 binding to MHC class I (21,22,28). Indeed, structural modeling demonstrated that ILT2 or ILT4 sterically interfere with CD8-α in binding to MHC class I (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interacting with MHC in the immunological synapse, a specialized junction between a T lymphocyte and an APC, CD8 can enhance the affinity of T-cell receptor (TCR)-CD8 complexes for MHC-peptide (pMHC) complexes by ∼10-fold (19). The importance of CD8 is also demonstrated by the function of two inhibitory receptors, ILT2 and ILT4, that can inhibit the function of CD8 by competing for MHC class I binding and generate T regulatory cells (20)(21)(22)(23)). …”
Section: Endritic Cells (Dcs) Are Potent Antigen-presenting Cells (mentioning
confidence: 99%
“…Colonies formed were observed through a phase-contrast microscope, and their numbers were counted on the third day for CFU-E and twelfth day for BFU-E, CFU-G, CFU-M, CFU-GM, and CFU-GEMM. In certain cases, 20 kBq of 3 H-thymidine (GE Healthcare) was added to the culture of 2 × 10 4 BMMCs for 8 hours, and its incorporation into an acid-insoluble fraction was measured by a beta-counter, Matrix 9600 (Packard), according to the described method (50).…”
Section: Figurementioning
confidence: 99%
“…The DNA fragments were inserted into pFUSE-hIgG1e3-Fc2 vector (InvivoGen, San Diego, CA). For the expression of PIR-A4 D1-D6 monomer, the plasmid was transfected to the DG44 cell (Invitrogen) and applied for gene amplification with methotrexate (Sigma) as described previously (20). For the expression of PIR-A4 D1D2 and D3-D6 Fc fusion protein, the plasmids were transfected to CHO-K1 cells.…”
Section: Preparation Of Recombinant Pir Domains-pir-b Likementioning
confidence: 99%
“…The fragment was inserted into pcDNA3.1 Zeo(ϩ) (Invitrogen). The resultant plasmid was further digested with BglII and NgoMIV to obtain CMV promoter-insert-poly(A) site fragment and ligated into pSV2-dhfr (ATCC) as described previously (20). PIR-A4 D1D2 and D3-D6 DNA fragments were amplified from PIR-A4 D1-D6 DNA-inserted pcDNA3.1 Zeo(ϩ) vector as a template with following primers: PIR-A4 (D1D2), 5Ј-CCATGGCCCTCCCTAAGCCTATCCTC-3Ј and 5Ј-CCATGGGGAGCTCCACGGATTCAC-3Ј; PIR-A4 (D3-D6), 5Ј-GATATCAGGTAATCTCCAAAAACCAACCAT-3Ј and 5Ј-GATATCGCTGAGACTGTGAGCTCCAC-3Ј.…”
Section: Preparation Of Recombinant Pir Domains-pir-b Likementioning
confidence: 99%